Thermal Mechanical Simulation of Corner Joint Configuration - Mohamad Hafiz Bin Mohd Hasan Abdullah, Mohamad Hafiz (Universiti Teknologi Petronas, 2010)
Welding is widely used in manufacturing industries to assemble various products. It is well known that welding process relies on an intensely localized heat input, which tends to generate undesired residual stresses and deformations in welded structures. Residual stresses are stresses that remain after the original cause of the stresses such as heat gradient during welding process. They remain along a cross section of the component even without external cause. This study has been conducted with objectives to develop finite element model of welding and compute temperature distribution and deformation of welded plate.